Heterosis, Inbreeding Depression and Inheritance of Seed Yield and its Component Traits in Safflower (Carthamus tinctorius L.) - Kumar, C. V. Sameer; Shivani, D.; Sreelakshmi, Ch.; Swarnalatha, V. (International Journal of Bio-resource and Stress Management, 2012)
The P1, P2, F1, F2, BC1 and BC2 of four safflower (Carthamus tinctorius L.) crosses were studied for eight metric traits. Individual scaling test and joint scaling test indicated that an additive dominance model was adequate in none of the cases. The results suggested that the presence of additive-dominance and epistatic gene effects for the traits indicating the importance of both additive and non-additive gene actions in the expression of these characters. Duplicate type of epistasis was prevalent in most of the cases. A substantial amount of heterosis over better parent was revealed in all the four crosses for seed yield and most of its attributes. Inbreeding depression was also significant for days to 50% flowering, days to maturity, number of capitula plant‑1 and test weight in the cross Manjira x GMU 1946 and HUS 305 x GMU 1946, whereas plant height and capitula plant-1 in the cross A1 x GMU 3272 and plant height, number of capitula plant-1, number of seeds capitulum-1 and test weight in the cross Manjira x GMU 12914-15. Suitable breeding strategies were suggested for the improvement of seed yield in safflower